Researching the Shifting Landscape of Adult Education in the Third World: New Perspectives on the Relationship between Adult Education and Democracy - Zelda Groener; Javier Corvalan; Irene Chadibe; Juan Madrigal (Adult Education Research Conference, 2000)
Recent democratisation in Chile and South Africa has impacted the relationship between adult education and democracy. At the same time however, adult education practices in the 50 year old Mexican democracy raises new questions. Four researchers from Chile, South Africa and Mexico share their perspectives on the relationship between adult education and democracy.